Complexity of management and health outcomes in a prospective cohort study of 573 heart failure patients in Australia: does more equal less?. Issue 11 (7th February 2013) - Driscoll, Andrea; Tonkin, Andrew; Stewart, Andrew; Worrall‐Carter, Linda; Thompson, David R; Riegel, Barbara; Hare, David L; Davidson, Patricia M; Mulvany, Christine; Stewart, Simon
<x xml:space="preserve">Abstract</x> Aims and objectives To compare the efficacy of chronic heart failure management programmes (CHF‐MPs) according to a scoring algorithm used to quantify the level of applied interventions–the Heart Failure Intervention Score (HF‐IS). Background The overall efficacy of heart failure programmes has been proven in several meta‐analyses. However, the debate continues as to which components are essential in a heart failure programme to improve patient outcomes. Design Prospective cohort study of patients participating in heart failure programmes. Method Forty‐eight of 62 (77%) programmes in Australia participating in a national register of CHF‐MPs were evaluated using the HF‐IS: derived from a summed and weighted score of each intervention applied by the CHF‐MP (27 interventions overall). The CHF‐MPs were prospectively categorised as relatively low (HF‐IS < 190 – n = 39 programmes & 407 patients) or high (HF‐IS ≥ 190 – n = 9 programmes & 166 patients) in complexity. Six‐month morbidity and mortality rates in 573 consecutively recruited patients with systolic dysfunction and in New York Heart Association Class II–IV were prospectively examined. Results Patients exposed to CHF‐MPs with a high HF‐IS had a lower rate of unplanned, all‐cause hospitalisation (n = 24, 14% vs. n = 102, 25%) compared with CHF‐MPs with a low HF‐IS within six months. On an adjusted basis, CHF‐MPs with a high HF‐IS were associated with a reduced risk of unplanned hospitalisation and/or death within six months and remained event‐free longer. Conclusion High complexity CHF‐MPs applying more evidence‐based interventions are associated with a higher event‐free survival over six months. Relevance to clinical practice The HF‐IS is an easy‐to‐use evidence‐based tool to assist programme coordinators to improve the quality of their heart failure programme which may also improve patient outcomes.